Novel X-Linked Inhibitor of Apoptosis Mutation in Very Early-Onset Inflammatory Bowel Disease Child Successfully Treated with HLA-Haploidentical Hemapoietic Stem Cells Transplant after Removal of αβ+ T and B Cells - Cifaldi, Cristina; Chiriaco, Maria; Di Matteo, Gigliola; Di Cesare, Silvia; Alessia, Scarselli; De Angelis, Paola; Rea, Francesca; Angelino, Giulia; Pastore, Maria; Ferradini, Valentina; Pagliara, Daria; Cancrini, Caterina; et al. (Frontiers in Immunology, 2017)
Monogenic defects in genes related to primary immunodeficiencies (PID) can be responsible for inflammatory bowel disease (IBD). Mutations in the X-linked inhibitor of apoptosis (XIAP) gene have been described in several patients suffering from IBD and, in particular, with very early-onset inflammatory bowel disease (VEOIBD) features. We report a VEOIBD child with a novel XIAP gene mutation characterized by a complicated disease course, which is unresponsive to several medical treatment options. An expanded genetic analysis including several PID genes performed by next-generation sequencing (NGS) was performed and revealed a de novo hemizygous mutation in XIAP gene: c.565T>C p.L189P. After mutation discovery, we investigated the XIAP protein expression and NOD2 signaling by western-blotting. Flow-cytometry was used to analyze intracellular protein expression in different cell subsets and T cell apoptosis. We observed reduced protein expression in lymphocytes, granulocytes, monocytes, an EBV-immortalized B cell line as well as increased apoptosis, and impairment in NOD2 signalling. The child was successfully treated with HLA-haploidentical HSCT, acquired from his mother, after ex vivo elimination of α/β T cells and CD19 B cells. One year after the transplant, we repeated the analysis to appreciate the changes in his impairments. The recovery of XIAP protein expression, function, and normalization of apoptosis were observed. Our report emphasizes the important role of genetic analysis in the diagnosis of VEOIBD, illustrates the complete immunological and gastrointestinal recovery after transplant and shows one of the few successful transplant cases of XIAP patients.